ICT expansion and human development: Empirical evidence from Indonesia - Sari, Vita Katika (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
Human development is a central focus and objective for countries worldwide. Comprehensive human development is reflected in rising living standards and easier access to essential services like education and health. Accelerating human development requires adopting technology, particularly ICT (Information and Communication Technologies), which is increasingly utilized by societies. The main objective of this study is to estimate the impact of ICT Skills, ICT Access, domestic investment, and the democracy index on the Human Development Index (HDI) using provincial-level data in Indonesia. The study employed panel data from 34 provinces from 2016-2022. Based on the Chow and Hausman test results, the fixed effect model was the best fit compared to the common and random effect models. The findings demonstrate that ICT Skills and ICT Access significantly positively affected human development throughout the research period, with their coefficients being almost equal. This highlights the rapid advancement of ICT and its vital role in the lives of the Indonesian population. The results further revealed that democracy was insignificant, while domestic investment positively and significantly impacted human development. Based on these findings, ICT development policies are essential, particularly in investment, infrastructure improvement, and the effective implementation of ICT initiatives. The use of ICT should be tailored to each province's unique characteristics and potential to promote equality and reduce disparities. A key recommendation from this study is the adoption of ICT in societal activities to enhance equality across all regions of Indonesia.